2022
DOI: 10.3390/mi13050806
|View full text |Cite
|
Sign up to set email alerts
|

O-Doping Configurations Reduce the Adsorption Energy Barrier of K-Ions to Improve the Electrochemical Performance of Biomass-Derived Carbon

Abstract: In recent years, atomic-doping has been proven to significantly improve the electrochemical performance of biomass-derived carbon materials, which is a promising modification strategy. Among them, there are relatively few reports about O-doping. Here, porous carbon derived from orange peel was prepared by simple carbonization and airflow-annealing processes. Under the coordination of microstructure and surface groups, the derived carbon had excellent electrochemical performance for the K-ion batteries' anode, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…28,29 OP mainly comprises cellulose, hemicellulose, pectin and lignin, which are known as good carbon precursors. It is reported that OP-derived carbon materials have been employed in catalysis, 30 gas sensors, 31 Pb–C mixed SCs, 32 LIBs/SIBs, 33 PIBs, 34 etc. However, most OPs are discarded and burned as waste due to the lack of effective and inexpensive synthesis methods, resulting in environmental pollution and resource waste.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 OP mainly comprises cellulose, hemicellulose, pectin and lignin, which are known as good carbon precursors. It is reported that OP-derived carbon materials have been employed in catalysis, 30 gas sensors, 31 Pb–C mixed SCs, 32 LIBs/SIBs, 33 PIBs, 34 etc. However, most OPs are discarded and burned as waste due to the lack of effective and inexpensive synthesis methods, resulting in environmental pollution and resource waste.…”
Section: Introductionmentioning
confidence: 99%